Clinical Rehabilitation Effect of Postoperative Lower-Limb Training on the Patients Undergoing OLIF Surgery: A Retrospective Study - Haoming Wang; Yachong Huo; Yachao Zhao; Botong Zhang; Dalong Yang; Sidong Yang; Wenyuan Ding (Pain Research and Management)
Background. In this study, it was aimed to investigate the clinical rehabilitation effect of lower-limb training on the patients that undergo oblique lumbar interbody fusion (OLIF) procedures. Methods. The eligible participants undergoing OLIF procedures between 01/2017 and 07/2019 were identified. All the patients underwent one-segment fusion operation (L3-4 or L4-5). Based on whether the participants received postoperative rehabilitation training, they were divided into two groups: intervention group and control group. Postoperatively, the participants in the intervention group were trained with lower-extremity rehabilitation exercise and maintained for three months. All participants got reexamined at the first postoperative week, the second postoperative week, the first postoperative month, and the third postoperative month (last follow-up). Comparisons were made in terms of the lower-extremity muscle force, visual analogue scale (VAS) score, lumbar JOA score, Oswestry disability index (ODI), the incidence of deep venous thrombosis (DVT), and patient satisfaction. Results. Seventy-seven participants in the intervention group (32 males and 45 females) and 82 in the control group (39 males and 43 females) were incorporated in this study. The median age of the participants was 57 years (39∼73) in the intervention group and 54 years (35∼71) in the control group. No statistical significance between the two groups was found (P>0.05). ODI score was less in the intervention group as compared to the control group in the first week after surgery (P=0.029). VAS and JOA scores were better in the intervention group in the first two weeks after surgery (P<0.05). DVT incidence in the intervention group was lower than the control group at final follow-up (P=0.037). Both group participants have achieved good grading in muscle force rehabilitation but no significant differences between the two groups. Additionally, satisfaction was higher in the intervention group than the control group. Conclusions. In summary, postoperative lower-extremity rehabilitation exercise can effectively accelerate patients’ health recovery from the OLIF surgery and increase their satisfaction.